Silver Nanoparticles Synthesized from Kenitu (Chrysophyllum caintio L.) Leaf Extract and Its Potential as Antibacterial Agents - Khoirunnisa, Aisy; Sutoyo, Suyatno (Pendidikan Kimia FKIP Universitas Jambi, 2024)
Currently, nanoparticles are one of the promising technologies and have been applied in various sectors. Silver nanoparticles is one of implementation in nanoparticles and have been applied in the industrial and medical. Green synthesis of silver nanoparticles is still in development. This method is carried out using plant extracts as bioreductors, because secondary metabolite compounds in extracts can reduce Ag+ ions into nanoparticle form. This study was conducted with the aim of determining the potential of Chrysophyllum caintio leaf extract as a bioreductor based on the UV-Vis sepctrophotometric instruments and to determine the potential of synthesized silver nanoparticles as antibacterial agents against Salmonella typhimurium through the disc diffusion method. The synthesis was carried out by volume ratio between kenitu leaf extract and AgNO3, 1:1, 1:2, 1:3, and 1:4. The result stated that the four variations have absorption in 422-465 nm. Where silver nanoparticles are formed can be known from the formation of peaks at a maximum wavelength of 400-500 nm. In a ratio of 1:2, a peak was formed at a wavelength of 453 nm with an absorbance of 0.758. Antibacterial activity in synthesized silver nanoparticles produced an inhibitory zone of 17.2 mm so it is classified as strong category.